2020
DOI: 10.1111/jcmm.15723
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback loop of ERK/CREB/miR‐212‐3p inhibits HBeAg‐induced macrophage activation

Abstract: The activation of liver macrophages is closely related to liver injury after HBV infection. Our previous results demonstrated that HBeAg played a key role in inducing macrophage activation. As we all know, miRNAs are involved in the regulation of multiple immune cell functions. Meanwhile, we have shown that miR‐155 positively regulates HBeAg‐induced macrophage activation and accelerates liver injury. Subsequently, based on our previous miRNA sequencing results, we further evaluated the role of miR‐212‐3p calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The immune responses triggered by HBcAg are illustrated in Figure 2. However, in our previous research, we found HBcAg could not effectively induce macrophage activation and participated in the liver damage caused by it (49)(50)(51). Therefore, HBcAg is a multifunctional protein, it is not only involved in viral nucleocapsid formation, but also associated with cccDNA epigenetic modulation and HBV immune evasion.…”
Section: Hbcagmentioning
confidence: 88%
“…The immune responses triggered by HBcAg are illustrated in Figure 2. However, in our previous research, we found HBcAg could not effectively induce macrophage activation and participated in the liver damage caused by it (49)(50)(51). Therefore, HBcAg is a multifunctional protein, it is not only involved in viral nucleocapsid formation, but also associated with cccDNA epigenetic modulation and HBV immune evasion.…”
Section: Hbcagmentioning
confidence: 88%
“…So far, only limited upstream regulators for miR-212-5p expression have been identified. 27 , 28 , 29 While a recent study showed that miR-212-5p was upregulated by hypoxia-inducible factor-1α (HIF-1α) in pancreatic cancer cells in hypoxia, 29 we do not know if HIF-1α mediates the upregulation of miR-212-5p in PASMCs in human PAH patients or rodents with PH, as the regulation of gene expression is always cell-type, tissue-type, and disease-background dependent. The cAMP-responsive transcription factor (CREB) has been recently identified as another transcriptional regulator for miR-212 in neuron cells, macrophages, or insulin-secreting β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP-responsive transcription factor (CREB) has been recently identified as another transcriptional regulator for miR-212 in neuron cells, macrophages, or insulin-secreting β-cells. 27 , 28 , 30 Recent studies showed that an extracellular cyclic AMP (cAMP)/CREB signaling in pulmonary arteries (including both smooth muscle and endothelial cells on the vessels) is activated to mitigate the severity of pulmonary vascular remodeling and PH 31 and that SMC-specific knockout of CREB induced pulmonary vessel wall thickening and PH in mice. 32 These findings not only revealed a protective mechanism that is activated during the pathogenesis of PH, but also led to our speculation that miR-212-5p is upregulated by CREB in PASMCs to play the protective role in PH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed gene set enrichment analysis (GSEA) of the IRF6 high and low expression groups to study the potential molecular mechanism of IRF6. The results showed that MAPK, ERBB, ERK and CREB pathways, which play important roles in the regulation of immune cells in the tumor environment [19][20][21][22], were significantly activated in the IRF6 high expression group (Figure 9). Thus, the above results demonstrated that the decrease of IRF6 expression was related to the alterations of tumor immune cells infiltration, which might affect the prognosis of ccRCC patients.…”
Section: Irf6 Expression Was Associated With Immune Cells Infiltration In Ccrccmentioning
confidence: 99%